Macro-economics : the measurement, analysis, and control of aggregate economic activity - Dernburg, Thomas Frederick; McDougall, Duncan M. (New York : McGraw-Hill, 1960)
This edition has the same twofold purpose as the first edition. First is to provide a fairly comprehensive survey of the subject matter included in junior or senior level course in aggregate economics. Second is that the authors have spanned the gap between the elementary and the professional level, proving a framework for more advanced study.
Includes bibliographical footnotes and index.
rpm 25/09/2017
Loans
Keywords: Income